Modelling UK inflation over the long run - Hendry, D (University of Oxford, 2000)
UK inflation varied greatly over 1865-1990, in response to many policy and exchange-rate regimes, two world wars and oil crises, and major legislative, and technological changes. It is modelled as responding to excess demands from all sectors of the economy: goods and services, factors of production, money, financial assets, foreign exchange, and government deficits, using indicator variables and commodity prices for special factors. Equilibrium-correction terms are developed for each of these. Variables representative of most theories of inflation mattered empirically over the sample, yielding an electric model which refutes any 'single cause' explanation